2004
DOI: 10.1016/j.febslet.2004.12.030
|View full text |Cite
|
Sign up to set email alerts
|

LDOC1, a novel MZF‐1‐interacting protein, induces apoptosis

Abstract: LDOC1 was isolated as a gene encoding a leucinezipper protein whose expression was decreased in pancreatic and gastric cancer cell lines in 1999. Here, we found that overexpression of LDOC1 caused externalization of the cell membrane phosphatidylserine, which was characteristic for early-phase apoptotic events, and reduced cell viability in some human cell lines. The apoptotic process was triggered by a loss of the mitochondrial membrane potential, leading to both caspase-3-dependent and -independent pathways.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 17 publications
2
41
0
Order By: Relevance
“…23,25,26 The observed downregulation of GNL3L by LDOC1 may significantly influence cell proliferation and apoptosis in mammalian cells. Recent reports suggest that LDOC1 is a novel regulator of NF-kB activity 23 and GNL3L acts as a mediator of NF-kB pathway, 27 but the mechanism remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,25,26 The observed downregulation of GNL3L by LDOC1 may significantly influence cell proliferation and apoptosis in mammalian cells. Recent reports suggest that LDOC1 is a novel regulator of NF-kB activity 23 and GNL3L acts as a mediator of NF-kB pathway, 27 but the mechanism remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…23,25,26 In order to define the effect of LDOC1 on GNL3L function during cell proliferation, we performed various in vitro functional assays. Flag-GNL3L and LDOC1-HA were transiently expressed in HEK293T cells and the rate of cell proliferation was analyzed using MTT assay.…”
Section: Ldoc1 Inhibits Gnl3l Functionmentioning
confidence: 99%
“…SPANX-C TAR clones also contain another gene, LDOC1, which has been shown to be down-regulated in some cancers (Nagasaki et al 1999;Inoue et al 2005). To investigate whether X-linked patients have mutational changes in this gene, ∼1.2-kb promoter and coding sequences were PCR amplified from TAR isolates (Supplemental Table 1S) and sequenced.…”
Section: Analysis Of Ldoc1 Did Not Reveal Any Mutations In the Codingmentioning
confidence: 99%
“…LDOC-1 is a known regulator of the nuclear factor (NF)-κB-mediated pathway of apoptosis through the inhibition of NF-κB (12). The expression of Wiskott-Aldrich syndrome protein family, member 3 induces the translocation of LDOC-1 from the nucleus to the cytoplasm, resulting in the inhibition of LDOC1-induced apoptosis (22,23). In addition, the transcription factor myeloid zinc finger gene 1 was demonstrated to interact with LDOC-1 and to enhance the activity of LDOC-1, thus favoring apoptosis (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of Wiskott-Aldrich syndrome protein family, member 3 induces the translocation of LDOC-1 from the nucleus to the cytoplasm, resulting in the inhibition of LDOC1-induced apoptosis (22,23). In addition, the transcription factor myeloid zinc finger gene 1 was demonstrated to interact with LDOC-1 and to enhance the activity of LDOC-1, thus favoring apoptosis (22,23). Recently, Buchholtz et al (24) observed a low expression of LDOC-1 in ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%